Ex vivo tumor dissection followed by kidney autotransplantation in bilateral wilms tumor - Zhong, Zhihai; Jiang, Hong; Chen, Huadong; Wu, Chenglin; Wang, Yuanqi; Zhang, Zhichong; Li, Jun; Liu, Juncheng (Frontiers in Pediatrics, 2023)
The challenge in managing bilateral Wilm’s tumor (BWT) lies in ensuring a radical resection while preserving enough normal kidney tissue. In children with huge or multiple tumors or tumors close to renal hilum after neoadjuvant chemotherapy, nephron sparing surgery often has a R1/R2 resection and high recurrence rate due to insufficient operational field exposure or massive blood loss. Kidney autotransplantation can completely resect the tumor while maintaining homeostasis and preserves the patient's own normal kidney tissues. Herein, we summarize the clinical data of 8 BWT patients who underwent kidney autotransplantation at the First Affiliated Hospital of Sun Yat-sen University from 2018 to 2020. Surgery was performed in stages or on both sides at once, depending on the child's condition. No residual tumors were found on postoperative imaging in all 8 children. All the postoperative complications were all transient and within the control, except for two patients with postoperative renal insufficiency due to combined DDS syndrome. During 38 months of follow-up, 87.5% (7/8) of patients were tumor-free survival with normal renal function. Only one patient died from renal failure without tumor recurrence. Therefore, our study indicated that autologous transplantation method after ex vivo tumor resection can completely remove the tumor in a bloodless state for BWT, especially in cases with large tumor size, multiple lesions and invasion of the renal pelvis. Autologous kidney transplantation can be an option for patients with complex BWT if the hospital's surgical technique and perioperative management conditions are feasible.